Avaliação do teste imunocromatográfico POC-CCA (África do Sul e Brasil) usado no diagnóstico para esquistossomose em residentes de área de alta endemicidade no nordeste do Brasil - Sousa, Maria Aparecida Alexandre (2020)
Schistosomiasis is a prevalent infection especially in poor and rural areas, which lack access to sanitation and to safe drinking water.The use of accurate diagnostic methods is important formapping of disease distributioncontributing to the implementation of schistosomiasis control strategies. The POC-CCA test for detection of circulating cathodic antigen of Schistosoma mansonihasbeen evaluated for use as a possible diagnostic tool.The aim of this study was to evaluate in an area of high prevalence for schistosomiasis, the results of the POC-CCA kits currently: Urine CCA (Schisto) ECO Teste distributed in Brazil by Eco Diagnostica (POC-CCA-BR) and Schisto POC-CCA manufactured and distributed by Rapid Medical Diagnostics (POC-CCA-AS). The study was conducted in the community of Siebra, rural area in of municipality of Maruim state of Sergipe. For the tests03 stool samples (Kato-Katz) and 01 urine sample (POC-CCA) was obtained, the strength of agreement between of tests was assessed by the kappa statistic. Sensitivity, specificity, accuracy and predictive values of the tests were estimated using the Kato-Katz as reference standard as well as the ROCcurve and AUC. The positivity for schistosomiasis mansoni obtained by the Kato-Katz technique(3 samples / 6 slides) was 48.82%, the POC-CCA-BR was 79.53%, considering the trace positive (t+) and 52.76% trace negative (t-) and with POC-CCA-AS 66.14% considering t + and 44.88% considering t-.The kits POC-CCA presented different sensitivities, specificities, predictive values and accuracy. There were divergences between the results of POC-CCA-BR and POC-CCA-AS, besides both tests showed false positives and false negatives in relation to Kato-Katz, with low Kappa index. In this study, there was a low agreement between the results of the POC-CCA kits currently available for diagnosing, compared to Kato-Katz and among themselves, even in a high prevalence area for schistosomiasis.The Kappa index of POC-CCA kits compared to Kato-Katz was 0.18 when t + and 0.48 when t- in POC-CCA-BR, in POC-CCA-AS it was 0.37 t + e 0.57 t-. When comparing the POC-CCA kits with each other, the Kappa index was 0.28 t + and 0.62 t-.